Aparatus Kritik Mustofa Al-Azmi pada Arthur Jeffery tentang Polemik Mushaf Ibnu Mas'ud : (Pendekatan Tekstologi) - Fathurrofiq Fathurrofiq (Sekolah Tinggi Ilmu Al-Quran Dan Sains Al-Ishlah, 2019)
Western scholars, often called, the orientalists somehow develope their Islam and or Quranic study based on their own methodology regardless the metholology achieved by muslim scholars. One of them was Arthur Jeffery. He explained his findings on Quranic codification made by muslim generation at that time had disconsidered variant readings of Quran. But Uthman proclaimed Jeffery Unified that variants by burning other codice and material belong to the prophet champanion. In the name of Ibnu Masud he found, actually such variants became indication of unautheticity of Uthman codice. Following the way of Jeffery thought, of course, muslim understanding on the Quranic autheticity will be disrupted. The muslim however mostly will confuse whether the naration on Usthman codice valid or not. The naration made by Jeffery on what he called as Ibnu Masud codice however will distructed the established understanding. In countering so, Mustofa al-Azmi came with bright explaination that the Quranic study belongs to Jeffery lack of muslim tradition i.e. strong transmission of Hadith. Mustofa al-Azmi sharply responded Jeffery by explaining three issues. Firstly, he told the weakness methodology of Jeffery on the different arrangement of surah belong to Ibnu Masud codice. Secondly, He refuted Jeffery’s misleading in the omitting three surah in codice belonged to Ibnu Masud. The third, the correction to Jeffery’s claim that he found difference or variant reading of Ibnu Masud codice from our codice that referred to Uthman codice. The way Mustofa Al Azmy refuse Jeffery it is the critical aparatus or textual apparatus of Mustofa al-Azmi.